2018
DOI: 10.1016/j.pmedr.2018.10.024
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating an insurer-based health coaching program: Impact of program engagement on healthcare utilization and weight loss

Abstract: Insurers and employers are increasingly offering lifestyle and weight-loss coaching programs; however, few evaluations have examined their effectiveness. Our objectives were to determine whether level of program engagement was associated with differences in healthcare utilization and weight pre/post coaching. We conducted a retrospective evaluation of enrollees in an insurer-based telephonic health coaching program in Maryland (2013–2014). Our independent variables were program engagement benchmarks (≥3 and ≥6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…49 Increasingly, health care systems, health insurers and employers are utilizing a wide range of "population health" approaches to improve health outcomes for the communities they serve, often through care management and health coaching. [50][51][52] A major strength of H42/H4U is its interface with prenatal care through the initial patient enrollment process and its remote delivery model. In our prior study evaluating the role of health care providers in a weight loss intervention, busy providers appreciated: 1) the remote delivery of the program, 2) having the coach (and not the provider) as the "interventionist" and 3)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Increasingly, health care systems, health insurers and employers are utilizing a wide range of "population health" approaches to improve health outcomes for the communities they serve, often through care management and health coaching. [50][51][52] A major strength of H42/H4U is its interface with prenatal care through the initial patient enrollment process and its remote delivery model. In our prior study evaluating the role of health care providers in a weight loss intervention, busy providers appreciated: 1) the remote delivery of the program, 2) having the coach (and not the provider) as the "interventionist" and 3)…”
Section: Discussionmentioning
confidence: 99%
“…Remotely delivered programs may reduce barriers to participant access and promote sustainability and implementation across multiple practices to ultimately enhance participant engagement 49 . Increasingly, health care systems, health insurers and employers are utilizing a wide range of “population health” approaches to improve health outcomes for the communities they serve, often through care management and health coaching 50–52 . A major strength of H42/H4U is its interface with prenatal care through the initial patient enrollment process and its remote delivery model.…”
Section: Discussionmentioning
confidence: 99%
“…Several health insurance plans, wellness programs, and pharmaceutical and medical device companies have started offering telephonic support in an attempt to help bridge the gap between patients and their health care providers. 9-12…”
Section: Telephonic Coachingmentioning
confidence: 99%
“…Previous studies have shown an association between coaching and engagement, specifically around selfmonitoring components of an intervention. [11][12][13] Therefore, multivariable regression modeling with normal distribution was performed to evaluate associations between coach-participant messages at 6 months and food logging, weigh-ins, and active minutes per week at 12 months, adjusting for participant characteristics of starting weight, gender, age, education, and engagement status. Multivariable logistic regression was also used to evaluate the association of coaching with the likelihood of being highly engaged.…”
Section: Secondary Analysismentioning
confidence: 99%
“…[5][6][7][8][9][10] Previous studies have also shown an association between coaching and engagement, specifically around self-monitoring components of an intervention. [11][12][13] Since only 20% of individuals are successful at weight loss maintenance at 12 months, determining factors and self-monitoring behaviors that promote successful weight loss and weight maintenance is essential for diabetes prevention. 14 Livongo DPP is a digital CDC-recognized program offering participants interactive lessons and live personal expert coaching.…”
Section: Introductionmentioning
confidence: 99%